Semantic complications in the war on terror discourse and manipulation of language by state and non-state actors - Khurshid, Ayisha; Hassan, Ahdi (International research journal of management, IT and social sciences, 2020)
Since September 11, 2001, attacks on the Twin Towers and the Pentagon, the US along with its allies declared War on Terror, where the binary opposition of ‘Us’ vs ‘Them’ was firmly established and channelized via both electronic and print media. The media’s discourse on the war against terrorism has been an intriguing research area for linguists as well as international relations experts. This paper highlights the problematization in defining a universally accepted definition of terrorism, the idiosyncratic nature of the War on Terror and how it differs from conventional wars, and, later how media, state and non-state actors (those labeled terrorists) use language to legitimize their views.